Innovation in Membrane-Based Batik Liquid Processing at Sekar Buen Batik Small and Medium Enterprises - Moch Purwanto; Rizka Ayu Yuniar; Rizka Lestari; Asful Hariyadi; Jefri Pandu Hidayat; Intan Dwi Wahyu Setyo Rini; Asri Prasaningtyas; Didik Kiswoyo (SWAGATI : Journal of Community Service, 2025)
The process of processing batik liquid waste using membrane technology has been implemented to overcome the problem of batik waste in the Sekar Buen Batik IKM Area through a community service program. The method used is the batik liquid waste filtration technique using a membrane. This community service activity is an effort to help strengthen the human resources of the batik industry community in the liquid waste processing process at the Sekar Buen Batik IKM located in North Penajam Paser. The activity has been carried out in several stages, including a preliminary survey, a discussion forum on batik waste problems with a partner team, making a design for a waste processing system based on membrane technology and working practices for the tool. This program can help partners in processing batik wastewater so that it can reduce its negative impact on the environment. The results of the program show that partners have an understanding of the technique of processing batik liquid waste based on membrane technology. Thus, industrial activities at the Sekar Buen Batik IKM can support the green industry area and be more environmentally friendly.